THE REPRESENTATION OF THE FIRST AND THE SECOND PERSON IN PETERPAN'S ALBUMS : The text analysis based on Critical Discourse Analysis - Dewi Nurlaela, - (2006)
This research investigates the representation of the first person, the second person, and hidden ideologybehind lyrics of Peterpan's albums. Under descriptive analysis, Critical Discourse Analysis of Fairclough, which is based on Systemic FunctionalGrammar of Hailiday, isemployed as analytical framework of this research. Eighteen lyrics from three of Peterpan's albums were takenas data of analysis. The lyrics portray the first and the second person written by Ariel as subject analysis, which were collected through purposive sampling. The research reveals that Ariel represents the first person as the one who is inactive and powerless person. On the other hand, the second person is represented as the one who has power and control over the first person. The ideology he wants to convey is a close relationship and intimacy. The intimacy he wants to convey is the close relationship between a person and other people. In addition, a person is a part of the society that needs other people in his/her life. IX